Abundance of microplastic in sediment around the west coast of Situbondo, East Java - Yona, Defri; Nabila, Risda Ayu; Fuad, Mochamad Arif Zainul; Iranawati, Feni (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Microplastic pollution has become a serious issue worldwide. Once it enters the environment, microplastics could accumulate in the water column and sediment. This study aimed to analyze the occurrence of microplastics in the beach sediments along the western coast of Situbondo, East Java. Sediment samples were collected in the strandline areas from seven different beaches that received the high impact of human activities. In the laboratory, sediment samples were oven-dried and weighed, density separation was performed using NaCl solution, degradation of organic matter was conducted using H2O2 30% and microplastic particles were identified using a microscope. In total, 1041 microplastic particles were retrieved from 21 sediment samples consisting of fiber (50 %), fragment (37 %), microbeads (11 %), and film (2 %). Microplastics found in this study consists of blue color (49 %), red (26 %), white (11 %), brown (7 %), and other colors such as yellow, black, green, and transparent with a percentage between 1?3 %. Microplastics with a size of < 300 µm dominate the result of this study. Microplastic abundances were found in the range of 204.52?492.50 particles/kg sediment sample. In each sampling location, the types of microplastic were found in a different pattern. Fiber and fragments were found in all sampling sites, while film and microbeads were found only in specific sites. This study showed that several factors, such as plastic sources and hydro-oceanography parameters, influenced the occurrence of microplastics in the sampling sites. In order to address microplastic pollution in the marine environment, plastic waste management strategies are required.Keywords: Fishing port, Mangrove, Marine Pollution, Plastics, Tourism